Association of PDYN 68-bp VNTR polymorphism with sublingual buprenorphine/naloxone treatment and with opioid or alcohol use disorder: Effect on craving, depression, anxiety and age onset of first use - Kaya-Akyüzlü, Dilek; Özkan-Kotiloğlu, Selin; Yalçın-Şahiner, Şafak; Ağtaş-Ertan, Ece; Özgür-İlhan, İnci (European journal of pharmacology, 2022)
In this case-control study (423 Turkish subjects), the functional pro-dynorphin (PDYN) 68-bp VNTR polymorphism was genotyped in opioid users receiving sublingual buprenorphine/naloxone treatment (SBNT; n = 129, 119 males and 10 females), in opioid users (OUD; n = 99, 90 males and 9 females), in alcohol users (AUD; n = 75, 75 males) and in controls (n = 120, 109 males and 11 females) to determine the effect of this polymorphism on different treatment responses, heroin or alcohol dependence as well as age onset of first use. The PDYN 68-bp alleles were determined based on the number of repeats and genotypes were classified as “short/short (SS)”, “short-long (SL)” and “long-long (LL)”. The intensity of craving, withdrawal, depression and anxiety were measured by the Substance Craving Scale (SCS), the Clinical Opiate Withdrawal Scale (COWS), the Beck Depression Inventory-II (BDI-II) and Beck Anxiety Inventory (BAI), respectively. Healthy controls (5.5 ± 5.8) had significantly lower levels of depressive symptoms compared to OUD (25.4 ± 13.5), AUD (22.5 ± 11.3) and SBNT (19.29 ± 12.2) groups. In OUD group, the LL genotype was associated with decreased intensity of anxiety and depressive symptoms than the SS+SL genotype. The BDI-II scores for PDYN VNTR genotypes within the 4 groups were analysed by two-way ANOVA and statistical differences were found for the groups. SBNT group had significantly lower COWS score than OUD group (1.00 versus 3.00). There were statistically significant differences in the median BAI (11 versus 24) and BDI-II scores (17.5 versus 25) between OUD and SBNT groups, supporting the antidepressant and anxiolytic effects of SBNT in persons with OUD. •PDYN 68-bp variations may have a prominent effect on buprenorphine treatment.•PDYN 68-bp S allele might be a risk factor for the increased craving and anxiety.•Extended treatment duration may be required to treat heroin addicts with S allele.•PDYN 68-bp variations may have an effect on the depressive-anxious symptomatology.•PDYN 68-bp repeat polymorphism seemed to affect the age onset of alcohol abuse.